Dinaciclib, a Cyclin-Dependent Kinase Inhibitor Promotes Proteasomal Degradation of Mcl-1 and Enhances ABT-737–Mediated Cell Death in Malignant Human Glioma Cell Lines - Jane, Esther P. (J Pharmacol Exp Ther, 2016)
The prognosis for malignant glioma, the most common brain tumor, is still poor, underscoring the need to develop novel treatment strategies. Because glioma cells commonly exhibit genomic alterations involving genes that regulate cell-cycle control, there is a strong rationale for examining the potential efficacy of strategies to counteract this process. In this study, we examined the antiproliferative effects of the cyclin-dependent kinase inhibitor dinaciclib in malignant human glioma cell lines, with intact, deleted, or mutated p53 or phosphatase and tensin homolog on chromosome 10; intact or deleted or p14ARF or wild-type or amplified epidermal growth factor receptor. Dinaciclib inhibited cell proliferation and induced cell-cycle arrest at the G2/M checkpoint, independent of p53 mutational status. In a standard 72-hour 3-[4,5-dimethylthiazol- 2yl]-5-[3-carboxymethoxyphenyl]-2-[4-sulfophenyl]-2H, tetrazolium (MTS) assay, at clinically relevant concentrations, dose-dependent antiproliferative effects were observed, but cell death was not induced. Moreover, the combination of conventional chemotherapeutic agents and various growth-signaling inhibitors with dinaciclib did not yield synergistic cytotoxicity. In contrast, combination of the Bcl-2/Bcl-xL inhibitors ABT-263 (4-[4-[[2-(4-chlorophenyl)-5,5-dimethylcyclohexen-1-yl]methyl]piperazin-1-yl]-N-[4-[[(2R)-4-morpholin-4-yl-1-phenylsulfanylbutan-2-yl]amino]-3-(trifluoromethylsulfonyl)phenyl]sulfonylbenzamide) or ABT-737 (4-[4-[[2-(4-chlorophenyl)phenyl]methyl]piperazin-1-yl]-N-[4-[[(2R)-4-(dimethylamino)-1-phenylsulfanylbutan-2-yl]amino]-3-nitrophenyl]sulfonylbenzamide) with dinaciclib potentiated the apoptotic response induced by each single drug. The synergistic killing by ABT-737 with dinaciclib led to cell death accompanied by the hallmarks of apoptosis, including an early loss of the mitochondrial transmembrane potential; the release of cytochrome c, smac/DIABLO, and apoptosis-inducing factor; phosphatidylserine exposure on the plasma membrane surface and activation of caspases and poly ADP-ribose polymerase. Mechanistic studies revealed that dinaciclib promoted proteasomal degradation of Mcl-1. These observations may have important clinical implications for the design of experimental treatment protocols for malignant human glioma.